Genome-wide data implicate terminal fusion automixis in king cobra facultative parthenogenesis - Daren C. Card; Freek J. Vonk; Sterrin Smalbrugge; Nicholas R. Casewell; Wolfgang Wüster; Todd A. Castoe; Gordon W. Schuett; Warren Booth (Scientific Reports, 2021)
Abstract Facultative parthenogenesis (FP) is widespread in the animal kingdom. In vertebrates it was first described in poultry nearly 70 years ago, and since then reports involving other taxa have increased considerably. In the last two decades, numerous reports of FP have emerged in elasmobranch fishes and squamate reptiles (lizards and snakes), including documentation in wild populations of both clades. When considered in concert with recent evidence of reproductive competence, the accumulating data suggest that the significance of FP in vertebrate evolution has been largely underestimated. Several fundamental questions regarding developmental mechanisms, nonetheless, remain unanswered. Specifically, what is the type of automixis that underlies the production of progeny and how does this impact the genomic diversity of the resulting parthenogens? Here, we addressed these questions through the application of next-generation sequencing to investigate a suspected case of parthenogenesis in a king cobra (Ophiophagus hannah). Our results provide the first evidence of FP in this species, and provide novel evidence that rejects gametic duplication and supports terminal fusion as a mechanism underlying parthenogenesis in snakes. Moreover, we precisely estimated heterozygosity in parthenogenetic offspring and found appreciable retained genetic diversity that suggests that FP in vertebrates has underappreciated evolutionary significance.